Politik Hukum Ketentuan Putusan Pailit Sebagai Dasar Pemberhentian Tidak Hormat Terhadap Jabatan Notaris - Qurratu Uyun Ramadani Zulkhainen (Officium Notarium, 2021)
The provisions regarding bankruptcy in Public Notary Law (UUJN) give rise to various interpretations since the Notary position is not regulated in the bankruptcy law. Therefore, two problem formulations were identified, namely: first, how to study the legal policy of the provisions of the bankruptcy decision as the basis for dishonoring the position of a Notary? Second, what is the impact of the bankruptcy decision as the basis for dishonorable discharge to the position of a Notary? This is a normative legal research with a statutory and conceptual approach. The results of this study conclude that first; political configuration tends to be democratic with a conservative character of legal products; and second, the impact of the bankruptcy provisions in the UUJN is divided into manifest impacts and latent impacts.Key Word: Legal Politics, Notary, Bankruptcy AbstrakKetentuan mengenai kepailitan di Undang-Undang Jabatan Notaris (UUJN) menimbulkan berbagai interpretasi. Sebab jabatan bukanlah objek yang diatur dalam undang-undang kepailitan. Oleh karena itu, diidentifikasi dua rumusan masalah, yaitu pertama, bagaimana kajian politik hukum ketentuan putusan pailit sebagai dasar pemberhentian tidak hormat terhadap jabatan Notaris? Kedua, apa dampak dari putusan pailit sebagai dasar pemberhentian tidak hormat terhadap jabatan Notaris? Jenis penelitian merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menyimpulkan pertama; konfigurasi politik cenderung demokratis dengan karakter produk hukum yang konservatif; dan kedua dampak dari ketentuan pailit di UUJN terbagi menjadi dampak manifes dan dampak laten.Kata-kata Kunci: Politik Hukum, Notaris, Kepailitan